MEMAHAMI MAKNA PRAKSIS PELAKSANAAN PEMBELAJARAN SEJARAH KONTROVERSIAL (History Department, Semarang State University and Historian Society of Indonesia, 2011)
There are many historical events in this country that is still laden with controversy, some of them are; G 30 S, the events surrounding Surat Perintah Sebelas maret, General Offensive March 1, 1949, the birth of Pancasila, the birth of the New Order, and integration of East Timor. Based on these facts, history learning should not only limit to narrative that is